Design and Construction of Domestic Oil and Fat Waste Processing as a Practical Tool for Practical Application in Waste Processing Technology in the DIII Industrial Chemistry Study Program - Permana, Edwin; Rahayu, Martina Asti; Lestari, Intan; Hidayat, Ali Nurdin (Proceeding International Conference on Religion, Science and Education, 2025)
Domestic wastewater is a liquid waste originating from household waste, including bathroom waste, kitchen waste, used water for washing food, and others. Before being discharged into the environment, domestic wastewater must first be processed in the Wastewater Treatment Installation Unit (IPAL) so as not to cause environmental pollution. One of the wastes that can cause water or rivers to smell is the high fat/oil content present in the water. One of the domestic wastewater treatment techniques is with a wastewater treatment installation (IPAL) by utilizing flotation techniques with physical and chemical filtration processes in the process principle. This process aims to remove solid particles that have low density, making it difficult to settle. Additionally, this tool does not require a large area and is easier to clean. In addition, this tool will also be a means of a tool for waste processing technology practicums in the Industrial Chemistry DIII Study Program.